THE CONCEPT OF ‘RURAL’ AS A PSYCHOSOCIAL PROCESS: FROM CONCEPT ATTAINMENT TO CONCEPT UNLEARNING - Dymitrow, Mirek (Quaestiones Geographicae, 2019)
Realising that human geography has been defined less by its canonical works but rather by its canonical concepts, the current status of the concept ‘rural’ puts a question mark over progress in human geography in terms of how well we have been able to adapt knowledge to reciprocate with societal change at large. As one of the oldest geographical concepts still in widespread use, ‘rural’ stands in stark contrast to the immense changes encountered by the society during the last century, let alone decades. And while this problem has been approached both empirically and philosophically, not enough stress has been put on the cognitive and sociological processes that have governed the attainment and retention of ‘rural’ in science, and beyond. In this vein, the aim of this paper is to provide a structured argument for facilitating a view of ‘rural’ less as a geographical space and more as a concept purportedly thought to define such space by way of inculcation.